Changes in the Arabic language curricula for the elementary stage in the city of Jerusalem in light of the policies of Israelization of education from the perspective of male and female teachers in private schools - Abu Sharif, Safaa Khalil (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to examine the extent of changes made to Arabic language curricula for the elementary stage in private schools in Jerusalem in light of education “Israelization” policies, as perceived by teachers. A mixed-methods approach was employed, combining qualitative semi-structured interviews with a descriptive analytical method that included content analysis of both the official Palestinian curriculum and the Israeli-modified version for grades one through six. The study population consisted of 209 Arabic-language teachers, while a purposive focus group of 25 teachers was selected for interviews. Findings revealed substantial alterations to the Arabic curriculum, particularly in grades 3–6, with no notable changes in grades 1 and 2. Moreover, 93% of the participants agreed that these Israelization-driven modifications aimed to weaken students’ linguistic competencies—especially grammar, spelling, and written expression—while ongoing curriculum changes contributed to declining academic achievement due to reduced stability and focus. Participants also emphasized the essential role of local communities and educational institutions in counteracting these policies through awareness efforts and advocating for unaltered alternative curricula. The study concludes by recommending the adoption of educational policies that reinforce national and cultural identity and safeguard the Arabic language against imposed curricular modifications.